OpenCL: an Alternative for Teaching Computer Architecture - Pereira, Fábio D.; Souza, Allan M. de; Moreno, Edward David (International Journal of Computer Architecture Education, 2013)
Teaching computer architecture, both conceptually and practically, is suitable for new multi/many-core architectures. This article highlights the application of the OpenCL platform in practical teaching of computer architecture, considering the use of CPU and GPU. The article also demonstrates application examples and performance comparison between CPU and GPU.